Phenotypic and WGS-derived antibiotic resistance patterns of Salmonella Enteritidis isolates from retail meat and environment during 2014 to 2019 in China - Zheng, Liya; Di, Qiannan; Xu, Xuebin; Liu, Liyuan; Qu, Chunbo; Bremer, Phil; Zhou, Xiujuan (Frontiers in Microbiology, 2025)
The emergence of multidrug-resistant (MDR) Salmonella Enteritidis has highlighted the importance of regularly monitoring for the occurrence of antibiotic-resistant strains. The current study combined phenotyping analysis and whole-genome-sequencing (WGS) to investigate the associations between the antibiotic-resistant phenotypes (ARPs) and genetic characteristics determinants in 95 Salmonella Enteritidis isolates from retail meat and environmental samples in China (2014–2019). Phenotypic analyses revealed that 70 isolates (73.68%) were MDR with 12 distinct resistance patterns. Most MDR strains (81.43%) had NAL-AMP-FIS-STR ± TET profiles, showing a fluctuating trend from 2015 to 2019, likely influenced by tetracycline withdrawal management. WGS identified four types of mutations in the gyrA gene were associated with nalidixic acid resistance. The co-carrying of blaTEM, sul2 and aph(6)-Id/aph(3″)-Ib was likely mediated by an X1-type plasmid, corresponding to resistance against ampicillin, sulfisoxazole, and streptomycin. Combining phenotypic analyses and WGS data, the 31 sequenced strains were primarily divided into two clusters, with most epidemic resistant strains in the largest cluster A. Identical ARP patterns observed across different sample types, regions, and isolation years but clustering together in cluster A suggested potential cross-contamination within the retail chain. Cluster B exhibited more diverse resistance patterns and genetic characteristics. Notably, three isolates in cluster B require special mention: a monophasic strain resistant to eight antibiotics, a strain exhibiting highly heteroresistance, and a strain with additional exotoxin genes. These results highlight the importance of ongoing surveillance and the utility of WGS to track and understand antibiotic resistance in Salmonella Enteritidis.